Chitosan-metal organic framework composite material as well as preparation and application thereof
By assembling the MOFs at open sites in situ on Fe3O4-chitosan composite microspheres, forming chitosan-metal organic framework composite materials, the low concentration and ionic interference of uranium extraction in seawater are solved, and high efficiency and selection are achieved uranium enrichment effect.
Patent Information
- Application Number
- CN202411561571.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art faces the problems of low concentration and ionic interference when extracting uranium from seawater, especially the interference of vanadium ions hinders the adsorption of uranium.
Fe3O4-chitosan composite microspheres were prepared by co-precipitation method, and metal organic frames (MOFs) with open sites were assembled in situ by solvothermal method to form a chitosan-metal organic frame composite material.
The composite material can efficiently enrich uranium elements in the solution, with a maximum adsorption capacity of 785.48 mg·g-1, and exhibits excellent selectivity and stability in seawater, solving the low concentration and ionic interference of uranium extraction in seawater question.
Smart Images

Figure CN119455908A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to preparation and application of a chitosan-metal organic framework composite material, belonging to the technical field of nuclear energy, and in particular to a chitosan in-situ assembled metal organic framework material with open sites and application thereof in uranyl ion enrichment. Background Art
[0002] In recent years, problems such as fossil fuel consumption and environmental protection have become increasingly prominent. Compared with traditional energy, nuclear energy is not only technologically mature, low-cost and highly efficient, but also different from renewable energy sources such as hydropower or photovoltaic power generation that are limited by natural conditions. Nuclear energy can ensure a stable power supply, thus becoming a sustainable energy source. Therefore, nuclear energy is regarded as a viable large-scale alternative to fossil fuels. Uranium is mainly used as fuel in nuclear reactions, but the known uranium reserves on land are only enough to support the operation of existing nuclear power plants for about 120 years. Studies have shown that the uranium content in seawater is about 4.5 billion tons, which is hundreds of times the reserves of uranium mines on land. Therefore, the development of technology to extract uranium from seawater is crucial for the future development of nuclear energy. However, this strategy faces two major challenges: 1) Low concentration: Due to limited solubility, the concentration of soluble uranium in seawater is only 3.3ppb; 2) Ion interference: The presence of various metal ions in seawater poses a major obstacle to uranium extraction, among which the interference of vanadium ions is particularly significant. Its structure and charge similar to uranium greatly hinder the adsorption of uranium.
[0003] Researchers have developed a variety of methods to extract uranium from seawater, including adsorption, electrochemical adsorption, membrane separation, and other technologies. Compared with other methods, adsorption has higher operating efficiency, wider applicability, and stronger economic feasibility. Several effective uranium adsorption materials have been reported, including graphene oxide, metal organic frameworks (MOFs), covalent organic frameworks (COFs), and Fe3O4 nanoparticle composites. Metal organic frameworks (MOFs) are very suitable as adsorbents due to their unique structure, surface chemistry, and composition. In the past three decades, researchers have developed composite materials suitable for various adsorption applications using the layered porous structure of MOFs. The application of MOFs in the adsorption process has many advantages, including excellent adsorption performance, good cyclic stability, and adjustable structure, which have been successfully applied to the enrichment of different metal ions. Although the use of MOFs to enrich uranium from seawater has been reported in the literature, this problem remains challenging due to the complexity of the seawater system, including ion interference and high salinity.
[0004] As a polysaccharide, chitosan exhibits remarkable multifunctional characteristics due to its excellent plasticity, cost-effectiveness, bioactivity and biocompatibility. The hydroxyl (-OH), amino (-NH2) and amide (-NH-CO) groups endow chitosan with efficient adsorption capacity for various cations, and researchers have successfully applied it to the capture of uranium. However, its sensitivity to acidic media, limited adsorption capacity and insufficient selection for specific metal ions greatly limit its practical application. Especially in complex marine systems or mineral environments, the effective capture of target ions based on chitosan materials is significantly restricted. Therefore, emerging research directions will focus on the development of new chitosan-based composite materials, with a special focus on integrating MOF into chitosan to form composite materials to enhance environmental adaptability, enhance adsorption capacity and improve selectivity. Summary of the invention
[0005] The purpose of the present invention is to construct a chitosan-metal organic framework composite material suitable for efficient enrichment of uranyl ions. First, Fe3O4-chitosan composite microspheres are prepared by coprecipitation, and ligands are further introduced to assemble MOFs with open sites by solvothermal method. The composite material can not only achieve efficient enrichment of uranium in solution, but also has a maximum adsorption capacity of 785.48 mg·g -1 , and has excellent selectivity for uranium, and can be further applied to the efficient enrichment of uranium in seawater.
[0006] The chitosan-metal organic framework composite material provided by the present invention is a magnetic microsphere assembled from chitosan and a metal organic framework, wherein Fe3O4 nanoparticles are distributed, and is synthesized by the following steps:
[0007] 1) Fe3O4@chitosan composite microspheres were prepared by coprecipitation method;
[0008] 2) MOFs were in situ assembled in Fe3O4@chitosan composite microspheres by solvothermal method.
[0009] Preferably, the chitosan-metal organic framework composite material is a magnetic microsphere with a particle size distribution of 1 to 2 mm, which includes Fe3O4 nanoparticles with a particle size distribution of 5 to 10 nm and MOFs with a particle size of 20 to 50 nm. MOFs and chitosan form molecular hydrogen bonds to stabilize the structure of the material.
[0010] Step 1) chitosan, Fe 2+ and Fe 3+The mixed solution is dropped into the NaOH solution, and its insolubility and co-precipitation mechanism are used to form Fe3O4@chitosan composite microspheres of uniform size. Due to the coordination between the iron ions and the amino groups of chitosan, the iron ions are evenly distributed on the chitosan microspheres. When the mixed solution is dropped into the NaOH solution, metal hydroxide (or oxide)-chitosan composite beads are generated because chitosan is insoluble in alkaline solution. The specific method can be: the chitosan is thoroughly dissolved in an acidic aqueous solution (such as a 5% acetic acid aqueous solution) by stirring, and the stirring speed is preferably 200-400 r min -1 ; and add FeCl2 and FeCl3 to completely dissolve, wherein the preferred amount of FeCl3 is 0.2 to 0.6 times the mass of chitosan, and the mass ratio of FeCl3 to FeCl2 is preferably 2:1; the resulting mixed solution is dripped into the NaOH solution through a syringe pump, and the flow rate is preferably 0.5 to 1 mL min -1 The concentration of the NaOH solution is preferably 0.5 to 2 mol L -1 After the addition is completed, the mixture is allowed to stand for a period of time, preferably 12 to 48 hours; the product is then washed with water until the pH value is a neutral solution, and dried for later use. The prepared Fe3O4@chitosan composite microspheres have an average particle size of 2 mm, a uniform particle size distribution, wrinkles and grooves formed on the surface, and exhibit magnetic properties.
[0011] Preferably, in step 2), 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine, 1,3,5-tris(4-carboxyphenyl)benzene, 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine, etc. are used as organic ligands, and trifluoroacetic acid is used as a protonating agent to achieve in situ assembly of MOFs in Fe3O4@chitosan composite microspheres by a solvothermal method. The specific method can be: dissolving 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine or other organic ligands in N,N-dimethylacetamide, wherein the concentration of the organic ligand is preferably 6-32 mg / L; adding Fe3O4@chitosan composite microspheres, preferably in an amount of 10-60 mg / L; and adding a protonating agent, such as trifluoroacetic acid, preferably in an amount of 4-16 μL / L, reacting in a reactor, preferably at a temperature of 120-180°C, and preferably for 12-48 hours; cooling to room temperature after the reaction is completed, washing with N,N-dimethylacetamide and ethanol for multiple times, and drying.
[0012] The present invention further provides a highly efficient enrichment method for uranium element, that is, using the chitosan-metal organic framework composite material of the present invention as a solid phase adsorption material to extract and enrich uranyl ions in a solution.
[0013] The carboxy chitosan-metal organic framework composite material of the present invention can effectively enrich the uranium element in the solution. The functional groups such as -COOH, -OH, -NH2 and C=N in the material play a key role as adsorption sites, and the adsorption capacity of uranyl ions is significantly improved. Taking the chitosan-metal organic framework composite material prepared in the embodiment of the present invention as an example, its maximum adsorption capacity for uranium element in pure water solution reaches 785.48 mg·g -1 , and better results were achieved under the enrichment conditions of pH = 5-10.
[0014] In a solution containing multiple competing metal ions, the chitosan-metal organic framework composite material of the invention can selectively adsorb uranium element.
[0015] In real seawater solution, the chitosan-metal organic framework composite material of the present invention can effectively enrich uranium in seawater. By utilizing magnetic separation technology and column separation, efficient enrichment of uranium in seawater systems can be achieved, and the recyclability, high specificity and environmental tolerance of the material are guaranteed, highlighting the potential of the material in seawater uranium extraction.
[0016] The present invention prepares chitosan-metal organic framework composite material by coprecipitation and subsequent solvothermal method, which has the advantages of simple synthesis, stable structure, acid and alkali resistance and salt resistance, etc. The material has wide application conditions, good selectivity and strong expansibility, and has potential practical application value in the field of uranium enrichment. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The figures are scanning electron microscope images and transmission electron microscope images of the chitosan-metal organic framework composite material synthesized in the embodiment, wherein: a)-c) are scanning electron microscope images of the cross section (100 μm), surface (2 μm) and cross section (200 nm) of the chitosan-metal organic framework composite material, respectively; d)-f) are transmission electron microscope images of the chitosan-metal organic framework composite material.
[0018] Figure 2 Hysteresis curves of Fe3O4@chitosan composite microspheres and chitosan-metal organic framework composites, where CS@Fe3O4 NPs represents Fe3O4@chitosan composite microspheres and CS@Fe3O4 NPs@PCN-333 represents chitosan-metal organic framework composites.
[0019] Figure 3 X-ray diffraction patterns of Fe3O4@chitosan composite microspheres and chitosan-metal organic framework composites, where CS@Fe3O4 NPs represents Fe3O4@chitosan composite microspheres, PCN-333 represents metal organic framework, and CS@Fe3O4NPs@PCN-333 represents chitosan-metal organic framework composites.
[0020] Figure 4 Infrared spectra of Fe3O4@chitosan composite microspheres and chitosan-metal organic framework composites, where (b) is an enlarged view of the shaded part of (a), CS represents chitosan, CS@Fe3O4 NPs represents Fe3O4@chitosan composite microspheres, CS@Fe3O4 NPs@PCN-333 represents chitosan-metal organic framework composites, and PCN-333 represents metal organic framework.
[0021] Figure 5 This is the adsorption curve of uranyl ions by the chitosan-metal organic framework composite material in Example 2.
[0022] Figure 6 This is a graph showing the selectivity of chitosan-metal organic framework composite materials for uranyl ion adsorption in Example 3.
[0023] Figure 7 This is a graph showing the adsorption effect of the chitosan-metal organic framework composite material in Example 4 on uranyl ions in seawater. DETAILED DESCRIPTION
[0024] The present invention is further described below by way of examples.
[0025] Example 1: Synthesis of chitosan-metal organic framework composite materials
[0026] (1) Synthesis of Fe3O4@chitosan composite microspheres. The specific preparation method is as follows:
[0027] 2.0 g chitosan powder was dissolved in 50 ml of 5% (w / w) acetic acid aqueous solution, and then 1.6 g FeCl3 and 0.8 g FeCl2 were added under continuous mechanical stirring and stirred for 2 hours until completely dissolved. After the dissolution was completed, the resulting solution was pumped through a syringe pump at 1 mL min -1 The product was added dropwise to 500 mL of 1M NaOH solution at a rate of 1.5 %. After standing for 12 hours, the product was washed with deionized water until its pH value was close to neutral. It was then dried at 80°C to obtain microspheres with a diameter of 2 mm and wrinkles and grooves on the surface.
[0028] (2) MOFs were assembled in situ in Fe3O4@chitosan composite microspheres by solvothermal method. The specific preparation method is as follows:
[0029] Accurately weigh 0.24 g of 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and dissolve it in 25 mL of N,N-dimethylacetamide, 0.36 g of the Fe3O4@chitosan composite microsphere sample obtained in step (1), and 400 μL of trifluoroacetic acid, add them into a 50 mL stainless steel polytetrafluoroethylene lined reactor, and react at 150°C for 24 hours. After the reaction is completed, wash with N,N-dimethylacetamide and ethanol five times respectively. Dry at 80°C, and the resulting microspheres with a diameter of 2 mm are the synthesized chitosan-metal organic framework composite materials.
[0030] Figure 1 Scanning electron microscope images and transmission electron microscope images of Fe3O4@chitosan composite microspheres and chitosan-metal organic framework composites are given, where a)-c) are scanning electron microscope images of the cross section (100μm), surface (2μm) and cross section (200nm) of the chitosan-metal organic framework composite, respectively, and d)-f) are transmission electron microscope images of the material, which verify the presence of Fe3O4 nanoparticles with a size of 5-10nm and octahedral MOFs with a size of 20-50nm in the material.
[0031] Figure 2 The hysteresis curves of Fe3O4@chitosan composite microspheres and chitosan-metal organic framework composites are given, and the magnetism decreases after the metal organic framework is assembled in situ, proving that the Fe3O4 nanoparticles are coated by the metal organic framework.
[0032] Figure 3 The X-ray diffraction patterns of Fe3O4@chitosan composite microspheres and chitosan-metal organic framework composites are given, proving the presence of Fe3O4 nanoparticles and metal organic frameworks.
[0033] Figure 4 The infrared spectra of Fe3O4@chitosan composite microspheres and chitosan-metal organic framework composites are given, proving the existence of molecular hydrogen bonds after the chitosan-metal organic framework composites are successfully assembled.
[0034] Example 2: Chitosan-metal organic framework composite material used as solid adsorbent to adsorb uranium
[0035] The experimental steps are as follows:
[0036] (1) Accurately weigh a certain amount of solid uranyl acetyloxy hexahydrate and dissolve it in pure water to prepare a uranyl ion concentration of 100 mg / L -1 The stock solution is ready for use.
[0037] (2) In parallel, 10 mg of the chitosan-metal organic framework composite solid adsorbent prepared in Example 1 was weighed into a polyethylene tube, and 50 mL of the uranyl solution prepared in step (1) diluted to a series of target concentrations was added.
[0038] (3) The pH value of the solution is adjusted to 5.5 by adding a negligible amount of nitric acid or sodium hydroxide solution.
[0039] (4) After mixing, shake thoroughly for 6 hours.
[0040] (5) After the shaking is completed, the supernatant is removed by magnetic separation and diluted in a certain ratio for testing.
[0041] (6) The uranyl ion content in the supernatant was determined by UV-visible spectrophotometry using azoarsine III dye (0.1%, w / v) as a colorimetric reagent.
[0042] (7) The uranyl ions in the supernatant were diluted and the concentration of uranyl ions in the solution was measured by inductively coupled plasma-mass spectrometry to verify the results.
[0043] Sorption (%) and adsorption capacity (q e ) is calculated as follows:
[0044]
[0045]
[0046] Where C0 and C e are the initial and equilibrium concentrations of uranyl ions in the solution, respectively, V is the volume of the solution, and m is the mass of the adsorbent.
[0047] (8) In each batch of experiments, a group without solid adsorbent was set up, and other experimental conditions remained the same, serving as the negative control group of the experiment.
[0048] (9) This experiment was a batch experiment and was carried out at room temperature.
[0049] The experimental results are as follows Figure 5 As shown in Figure 2, the saturated adsorption capacity of chitosan-metal organic framework composite materials for uranyl ions is 785.48 mg·g -1 .
[0050] Example 3: Experiment on selectivity of chitosan-metal organic framework composite materials
[0051] The specific steps are as follows:
[0052] (1) Prepare stock solutions of different metal ions with mass concentrations shown in Table 1, including 8 different ions: magnesium (II), calcium (II), sodium (I), potassium (I), Fe (II), vanadium (II), europium (III), and uranium (II).
[0053] Table 1 Concentration of different ions
[0054]
[0055] (2) The adsorption experiment process is consistent with that in Example 2.
[0056] (3) After centrifugation, the supernatant was diluted to an appropriate multiple, and the concentrations of different ions were detected using inductively coupled plasma-mass spectrometry.
[0057] (4) The distribution coefficient of the material for different ions (K d ) is calculated as follows:
[0058]
[0059] Where C0 and C e are the initial and equilibrium concentrations of uranyl ions in the solution, respectively, V is the volume of the solution, and m is the mass of the adsorbent.
[0060] The experimental results are as follows Figure 6 As shown in Figure 2, the chitosan-metal organic framework composite material exhibits excellent selectivity for uranyl ions in solutions with different ions (K d The value is about 58000mL·g -1 ).
[0061] Example 4: Adsorption experiment of uranium in seawater samples using chitosan-metal organic framework composite materials
[0062] The specific steps are as follows:
[0063] Natural seawater (Bohai Sea, Weihai) was filtered to remove large particles and impurities, and then the chitosan-metal organic framework composite material was used for adsorption experiments. After adsorption, the concentrations of different ions were detected by plasma-mass spectrometry.
[0064] The results of the test are as follows Figure 7 As shown, the material can adsorb more than 90% of uranyl ions in simulated seawater samples.
Claims
1. A chitosan-metal organic framework composite material, which is a magnetic microsphere assembled by chitosan and a metal organic framework, wherein Fe3O4 nanoparticles are distributed, wherein Fe3O4@chitosan composite microspheres are first synthesized by a coprecipitation method, and then MOFs are in situ assembled in the Fe3O4@chitosan composite microspheres by a solvothermal method to obtain the chitosan-metal organic framework composite material, wherein molecular hydrogen bonds are formed between the in situ assembled MOFs and chitosan.
2. The chitosan-metal organic framework composite material according to claim 1, characterized in that: The chitosan-metal organic framework composite material is a magnetic microsphere with a particle size distribution of 1-2 mm, which includes Fe3O4 nanoparticles with a particle size distribution of 5-10 nm and MOFs with a particle size distribution of 20-50 nm.
3. The method for preparing the chitosan-metal organic framework composite material according to claim 1 or 2, comprising the following steps: 1) Fe3O4@chitosan composite microspheres were prepared by coprecipitation method; 2) MOFs were in situ assembled in Fe3O4@chitosan composite microspheres by solvothermal method.
4. The preparation method according to claim 3, characterized in that: Step 1) chitosan, Fe 2+ and Fe 3+ The mixed solution was added dropwise into NaOH solution, and Fe3O4@chitosan composite microspheres with uniform size were formed by utilizing its insolubility and co-precipitation mechanism.
5. The preparation method according to claim 4, characterized in that: Step 1) Chitosan is thoroughly dissolved in an acidic aqueous solution by stirring, and FeCl2 and FeCl3 are added to completely dissolve, and the resulting mixed solution is dripped into a NaOH solution through a syringe pump. After the dripping is completed, it is allowed to stand and age for a period of time, and then the product is washed with water until the pH is neutral, and dried for later use.
6. The preparation method according to claim 5, characterized in that: In step 1), the acidic aqueous solution is a 5% acetic acid aqueous solution, the mass ratio of the added FeCl3 and FeCl2 is 2:1, and the concentration of the NaOH solution is 0.5-2 mol L -1 .
7. The preparation method according to claim 3, characterized in that: Step 2) Using 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine, 1,3,5-tris(4-carboxyphenyl)benzene or 2,4,6-tris[(p-carboxyphenyl)amino]-1,3,5-triazine as organic ligands and trifluoroacetic acid as a protonating agent, the in situ assembly of MOFs in Fe3O4@chitosan composite microspheres was achieved by a solvothermal method.
8. The preparation method according to claim 7, characterized in that: In step 2), the solvent used is N,N-dimethylacetamide, the concentration of the organic ligand is 6-32 mg / L, the amount of Fe3O4@chitosan composite microspheres added is 10-60 mg / L, and the reaction temperature is 120-180°C.
9. A method for enriching uranium, comprising using the chitosan-metal organic framework composite material according to claim 1 or 2 as a solid phase adsorption material to perform solid phase extraction on uranyl ions in a solution.
10. The method for enriching uranium as claimed in claim 9, characterized in that: The solution is sea water.